Method for producing fluorapatite crystals

JP2024509356A5Active Publication Date: 2025-01-22NANO DENTICA AB
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023545207
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-01-28
Filing Date
2022-01-27
Publication Date
2025-01-22
Estimated Expiration
2042-01-27

AI Technical Summary

Technical Problem

Existing methods for producing fluoroapatite crystals are impractical for industrial applications due to long reaction times, high temperatures, atmospheric pressures, and pH adjustments, limiting their scalability and ability to produce nanofluoroapatite crystals.

Method used

A method involving the mixing of supersaturated phosphate and fluoride sources with a calcium source at room temperature, without pH adjustment, allows for rapid formation of fluoroapatite crystals within minutes, enabling the production of nanofluoroapatite and microfluoroapatite crystals.

Benefits of technology

This method facilitates rapid, scalable, and cost-effective production of fluoroapatite crystals with various morphologies and sizes, reducing energy and water usage, and is environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

A method for producing fluorapatite crystals is provided, the method comprising the steps of: a) providing a first aqueous solution comprising a phosphate source and a fluoride source, the first aqueous solution being supersaturated with respect to the pentaphosphate source and the fluoride source; b) providing a second aqueous solution comprising a calcium source, the second aqueous solution being undersaturated with respect to the calcium source; c) mixing the first and second aqueous solutions, thereby providing a mixture comprising fluorapatite crystals and a further aqueous solution 10; d) optionally stirring the mixture of step c); e) optionally heating the mixture of step c) and / or step d); f) separating the fluorapatite crystals from the further aqueous solution; g) optionally drying the fluorapatite crystals of step f); and 15h) optionally grinding the fluorapatite crystals obtained in step f) or step g). Figure 1 for publication.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for producing fluoroapatite crystals, which can be nano-fluoroapatite crystals or micro-fluoroapatite crystals.The present disclosure also relates to the use of said fluoroapatite crystals for producing liners, sealers, ceramic materials, dental restorative products, filling materials such as dental cement compositions, dental coatings, implants, or medical devices. [Background technology]

[0002] Fluorapatite (Ca5(PO4)3F) is the most common phosphate mineral found widely along the Earth's crust and plays an important role in the soil fertilizer industry. It is also found in the form of complex, compact structures in the surface layer of the dentition of sharks, which are specialized for hunting and biting (Reference 1). Fluorapatite does not naturally occur in the human dentition. Instead, it is hydroxyapatite (Ca5(PO4)3OH) that is present in the surface layer, or enamel (Reference 1).

[0003] In stomatology, its main use is related to its ability to prevent dental caries, either by fluoridation of water or by topical application of fluoride-containing products (toothpastes, varnishes, mouthwashes, etc.). The World Health Organization has reported that water fluoridation can significantly reduce the risk of dental caries in children, by reducing the amount of fluoride in the most superficial layer of enamel during tooth formation and subsequent eruption. -states that fluoride is associated with higher concentrations of hydroxyapatite, which indicates the presence of fluoroapatite (Reference 2). Additionally, topical application of fluoride has been shown to be reflected in the conversion of hydroxyapatite to fluoroapatite on the most superficial layers of enamel, specifically a few atomic layers (Reference 3). Furthermore, fluoroapatite may be useful in the management and prevention of secondary caries (SC). Recent studies have shown that SC correlates with Class II composite restorations in patients who smoke and are at high risk for caries. Additionally, SC may affect up to 20% of patients in private practice, where the most common treatment is replacement of restorations (Reference 4). It is a frustrating and costly process for both patients and clinicians.

[0004] Various techniques for the synthesis of powdered fluorapatite have been described. For example, Montel G. in 1958 showed in his doctoral thesis that fluorapatite can be produced by a solid-state reaction involving a mixture of calcium fluoride (CaF2) and tetracalcium phosphate (TCP) or calcium pyrophosphate (Ca2P2O7) heated at 900 °C for 2 hours. The same authors showed that fluorapatite can be produced by a hydrothermal reaction. A typical reaction uses disodium phosphate (Na2HPO4) and calcium chloride (CalCl2) in ammonia to synthesize dicalcium phosphate dihydrate (CaHPO4.2H2O). Then calcium chloride (CalCl2) and sodium fluoride (NaF2) produce calcium fluoride (CaF2). Then dicalcium phosphate dihydrate (CaHPO4.2H2O) and calcium fluoride (CaF2) are mixed and stirred constantly at 50 rpm at room temperature for 5 days. Montel G. reported that a faster reaction can be obtained by mixing dicalcium phosphate dihydrate (CaHPO4.2H2O) with sodium fluoride (NaF2) (Reference 5).

[0005] Later, in 1962, Farr TD et al. documented that fluorapatite could be obtained after equilibration of phosphoric acid (H3PO4), alpha-tetracalcium phosphate (α-TCP), monocalcium phosphate (MCPM), and calcium fluoride at 50°C for 7 months (Reference 6). By 2006, Kniep R and Simon P introduced the use of nucleating agents as a key factor for synthesis. For example, 2-20 μm fluorapatite (rod-shaped, fan-shaped, and spherical) could be produced by using pigskin gelatin as a nucleating and growing agent and diffusing two solutions into the central gelatin. The solutions are typically calcium chloride (CalCl2) as the calcium source, and disodium phosphate (Na2HPO4) and potassium fluoride (KF) as the phosphate and fluoride sources. Both solutions were adjusted to a pH of 7.4. The reaction is carried out at 25°C to 30°C for three weeks (Reference 7).

[0006] Chen H et al. also reported the use of ethylenediaminetetraacetic acid (EDTA), a chelating agent, in 2006. Fluorapatite powder is produced by mixing calcium disodium salt of ethylenediaminetetraacetic acid (EDTA-Ca-Na2) and sodium phosphate dihydrate (Na2HPO4.H2O). The pH of the solution is adjusted to 6.0 with sodium hydroxide (NaOH). Sodium fluoride (NaF) solution is then added and stirred at room temperature for a few minutes. The mixture is then autoclaved at 121°C and 2.37 atm for 5 minutes to 10 hours (Reference 8).

[0007] Chen M et al. in 2009 introduced the use of citric acid to produce fluorapatite. It is mixed with disodium ethylenediaminetetraacetate (Na2EDTA) and kept in a water bath at 40°C. Calcium nitrate (Ca(NO3)2), diammonium phosphate ((NH4)2HPO4), and sodium fluoride (NaF) are then added under constant stirring. The pH is adjusted to 5.2 using sodium hydroxide (NaOH). The mixture is then stirred for 20 minutes and then autoclaved at 150°C for 8 hours (Reference 9).

[0008] Clarkson BH and Chen H patented a method (US7879388B2) in 2011 in which hydroxyapatite itself is used as the starting source of calcium and phosphate to produce fluorapatite powder. Hydroxyapatite is mixed with sodium fluoride and both are dissolved using nitric acid. The pH is then adjusted to 6-11 using ammonium hydroxide. The solution is then left in a water bath at 25-70°C for 5 days (Reference 10).

[0009] Wang H et al. reported in 2011 that fluorapatite crystals can be produced by using acetic acid. A calcium chloride (CalCl2) solution is mixed with a sodium phosphate dodecahydrate (Na2HPO4.12H2O) and sodium fluoride (NaF) solution. Acetic acid and sodium hydroxide are used to maintain the pH of the solution below 6. The two solutions are mixed and kept in a water bath at 37°C for 1 to 5 weeks (Reference 11).

[0010] More recently, in 2014, Furukawa A obtained a patent (JP2014 / 181160A) for a method for producing fluorapatite crystals that can be produced by constant stirring of two solutions mixed by a dropping funnel. Typically, the calcium source is calcium chloride dihydrate (CalCl2.2H2O) and adjusted to pH=5.0 by hydrochloric acid (HCl). The phosphate and fluoride solution is typically a combination of diammonium phosphate ((NH4)2HPO4) or dihydrogen phosphate H(H2PO4) and sodium fluoride (NaF2), whose pH is also adjusted to 5.0 by hydrochloric acid (HCl). The reaction is carried out by standing at 50° for 1 hour, where the pH of the reaction is adjusted to 5.0 or less. The solutions can be added to each other by a dropping funnel or into an aqueous solution at the above-mentioned temperatures. The resulting fluorapatite crystals are bundle-like and require an additional step of dispersion using polyphosphate and a shaking treatment with zirconia beads for 6 hours (Reference 12).

[0011] The great value that fluoroapatite represents for preventive and restorative dentistry is limited by the industrial ability to produce the powder by simple and rapid methods. For example, the method proposed by Montel G. is carried out at room temperature but requires constant stirring at 50 rpm and a reaction time of 5 days, a reaction time that is impractical for industrial applications.

[0012] The method reported by Farr TD et al. involves a process with a reaction time of 5 months, a reaction time that is not feasible for industrial applications.

[0013] The method documented by Kniep R and Simon P uses gelatin skins, a 3 week reaction time, requires pH adjustment, and can only produce microcrystals, a process that cannot produce nano fluorapatite and has reaction times that are too long for industrial purposes.

[0014] The method described by Chen H et al. requires increased atmospheric pressure (2.37 atm) at 121° C. and a reaction time that can last for 10 hours. It is a complex process with limited industrial scalability.

[0015] The method presented by Chen M et al. requires pH adjustment, atmospheric pressure increase in an autoclave, and 150 °C with a reaction time of 8 h, and is a complicated process with limited industrial scalability.

[0016] The method reported by Clarkson BH and Chen H (US7879388B2) requires pH adjustment and a reaction time of 5 days, making it rather unfeasible for industrial application.

[0017] The method documented by Wang H et al. requires pH adjustment and reaction times of 1-5 weeks, which are too long for industrial purposes.

[0018] The method described by Furukawa A (JP2014 / 181160A) requires pH adjustment and constant stirring for 1 hour, and cannot produce individual nano-fluoroapatite crystals. The structure produced is bundled and requires 6 hours of grinding with polyphosphoric acid to produce individual crystals. The method lacks simplicity and requires grinding to produce individual nano-fluoroapatite crystals, and also lacks the ability to produce micro-fluoroapatite crystals.

[0019] Most of the above mentioned methods are naturally based on the reactants proposed by Montel G in 1958. However, they require pH adjustment, constant stirring, extensive grinding, reaction temperatures above 100° C., and / or increased atmospheric pressure. Therefore, they are still expensive procedures on an industrial scale, and their fluorapatite powders are still unavailable to professionals and patients.

[0020] None of them can produce individual nano-fluoroapatite crystals immediately after mixing two solutions and stirring for 1 minute as proposed in this patent, and none of them can produce individual micro-fluoroapatite crystals after 10 minutes at 70°C. Furthermore, they do not require pH adjustment, constant stirring, and long reaction temperatures and / or high pressures. This method is more suitable for large-scale production and industrial scalability.

[0021] Additionally, one of the goals strategized by the United Nations General Assembly in 2015 is the Sustainable Development Goal (Goal 9 or SDG 9), which aims to build resilient infrastructure, promote sustainable industrialization, and encourage innovation. One of the mechanisms to achieve this goal is to upgrade all industries and infrastructure for sustainability, strengthen research, and upgrade industrial technology.

[0022] The listing or discussion of an apparently prior-published document in this specification should not necessarily be taken as an acknowledgement that the document is part of the state of the art or is common general knowledge.

[0023] It is an object of the present disclosure to overcome or at least alleviate one of the above problems, and further to provide advantages and / or aspects not provided by the previously known art. Summary of the Invention

[0024] The above object can be achieved using a method for producing fluoroapatite crystals according to claim 1. A method for preparing a dental or non-dental composition according to claim 16 is also provided. Furthermore, the use of fluoroapatite crystals produced according to the method for producing fluoroapatite crystals described herein is provided. Variations of the present disclosure are described in the dependent claims and in the following description. [Brief description of the drawings]

[0025] [Figure 1] 1 illustrates a method for producing fluorapatite crystals as described herein. [Figure 2A] 1 shows an SEM image of the powder described in Example 1. [Figure 2B] 1 shows an SEM image of the powder described in Example 2. [Figure 2C] 1 shows an SEM image of the powder described in Example 3. [Figure 2D] 1 shows an SEM image of the powder described in Example 4. [Figure 3A] 1 shows a TEM image of the powder described in Example 1. [Figure 3B] 1 shows a TEM image of the powder described in Example 1. [Figure 3C] 4 shows a TEM image of the powder described in Example 2. [Figure 3D] 4 shows a TEM image of the powder described in Example 2. [Figure 4-1] Graph 1 - Shows the XRD of the powder described in Example 1. [Figure 4-2] Graph 2 - Shows the XRD of the powder described in Example 1. [Figure 4-3] Graph 3 - Shows the XRD of the powder described in Example 2. [Figure 4-4] Graph 4 - Shows the XRD of the powder described in Example 2. [Figure 4-5] Graph 5 - Shows the XRD of the powder described in Example 3. [Figure 4-6] Graph 6 - Shows the XRD of the powder described in Example 4. [Diagram 4-7] Graph 7 - Shows the XRD of the mineral fluorapatite described herein. [Figure 5-1] Graph 1 - RS spectrum of the powder described in Example 1. [Figure 5-2] Graph 2 - RS spectrum of the powder described in Example 1. [Figure 5-3] Graph 3 - RS spectrum of the powder described in Example 2. [Figure 5-4]Graph 4 - RS spectrum of the powder described in Example 2. [Figure 5-5] Graph 5 - RS spectrum of the powder described in Example 3. [Figure 5-6] Graph 6 - RS spectrum of the powder described in Example 4. [Figure 5-7] Graph 7 - RS spectrum of the mineral fluorapatite described herein. [Figure 6-1] Graph 1 - Shows an EDS image of the powder described in Example 1. [Figure 6-2] Graph 2 - Shows an EDS image of the powder described in Example 2. [Figure 6-3] Graph 3 - Shows an EDS image of the powder described in Example 3. [Figure 6-4] Graph 4 - Shows an EDS image of the powder described in Example 4. [Figure 7A] 1 shows an SEM image of the pellets described in Example 5. [Figure 7B] 13 shows an SEM image of pellets after immersion in artificial saliva as described in Example 5. [Figure 7C] 1 is an RS spectrum of the polymer-based cement described in Example 5. [Figure 8A] 1 shows an SEM image of the dried pellets described in Example 6. [Figure 8B] 13 shows SEM images of pellets subjected to deionized water and artificial saliva as described in Example 6. [Figure 8C] 1 shows the RS spectrum of the water-based cement described in Example 6. [Figure 9A] 1 shows a pellet of microliner containing the ethanol-based 10-MDP-containing adhesive described in Example 7 after soaking in deionized water. [Figure 9B] 13 shows a pellet of microliner containing ethanol-based 10-MDP-containing adhesive as described in Example 7 after immersion in artificial saliva. [Figure 9C]1 shows a pellet of microliner containing water-based 10-MDP-containing primer and ethanol / water-free adhesive as described in Example 7 after immersion in deionized water. [Figure 9D] 13 shows a pellet of microliner containing water-based 10-MDP-containing primer and ethanol / water-free adhesive as described in Example 7 after immersion in artificial saliva. [Figure 9E] 13 shows a pellet of microliner containing the total etch ethanol based adhesive described in Example 7 after immersion in deionized water. [Figure 9F] 13 shows a pellet of microliner containing a total etch ethanol-based adhesive as described in Example 7 after immersion in artificial saliva. [Figure 9G] 13 shows a pellet of microliner containing total etch adhesive water-based adhesive as described in Example 7 after immersion in deionized water. [Figure 9H] 13 shows a pellet of microliner containing the total etch water-based adhesive adhesive described in Example 7 after immersion in artificial saliva. [Figure 10-1] Graph 1 - Shows EDS images of pellets of microliner containing ethanol-based 10-MDP-containing adhesive as described in Example 7 after immersion in artificial saliva. [Figure 10-2] Graph 2 - Shows EDS images of pellets of microliner containing water-based 10-MDP-containing primer and ethanol / water-free adhesive as described in Example 7 after immersion in artificial saliva. [Figure 10-3] Graph 3 - Shows EDS images of pellets of microliner containing total etch ethanol based adhesive as described in Example 7 after immersion in artificial saliva. [Figure 10-4] Graph 4 - Shows EDS images of pellets of microliner containing total etch water-based adhesive adhesive as described in Example 7 after immersion in artificial saliva. [Figure 11] 1 shows an SEM image of the interface between a microliner with an ethanol-based 10-MDP-containing adhesive and dentin. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] The present disclosure provides a method for producing fluorapatite crystals, the method comprising: a) providing a first aqueous solution comprising a phosphate source and a fluoride source, the first aqueous solution being supersaturated with respect to the phosphate source and the fluoride source; b) providing a second aqueous solution comprising a calcium source; c) mixing the first aqueous solution with the second aqueous solution, thereby providing a mixture containing fluorapatite crystals and a further aqueous solution; d) optionally stirring the mixture of step c); e) optionally heating the mixture of step c) and / or step d); f) separating the fluorapatite crystals from the further aqueous solution; g) optionally drying the fluoroapatite crystals of step f); h) optionally, grinding the fluorapatite crystals obtained in step f) or step g).

[0027] The second aqueous solution can be unsaturated with respect to the calcium source. Thus, a method for producing fluorapatite crystals is provided, the method comprising: a) providing a first aqueous solution comprising a phosphate source and a fluoride source, the first aqueous solution being supersaturated with respect to the phosphate source and the fluoride source; b) providing a second aqueous solution comprising a calcium source, the second aqueous solution being unsaturated with respect to the calcium source; c) mixing the first aqueous solution with the second aqueous solution, thereby providing a mixture containing fluorapatite crystals and a further aqueous solution; d) optionally stirring the mixture of step c); e) optionally heating the mixture of step c) and / or step d); f) separating the fluorapatite crystals from the further aqueous solution; g) optionally drying the fluorapatite crystals of step f); h) optionally, grinding the fluorapatite crystals obtained in step f) or step g).

[0028] It will be appreciated that step c) of the method described herein may be carried out at room temperature, for example at about 20°C to about 25°C, for example at 20°C ± 2°C. It will further be appreciated that the method described herein may be carried out at room temperature and / or may not include a pH adjuster. Furthermore, the method may be carried out with little stirring, for example for 60 minutes or less, for example 5, 10, 15, 20, 25 or 30 minutes. Surprisingly, it has been found that the method allows for rapid formation of fluorapatite crystals, for example for formation of fluorapatite crystals in 1 hour or less, for example about 10 minutes, for example within about 1 minute. Furthermore, the method allows for the production of fluorapatite crystals of various morphologies and / or sizes, for example nano-fluorapatite crystals or micro-fluorapatite crystals. The method also allows for reduced water usage. Furthermore, the method allows for reduced energy usage, since it may be carried out at room temperature. As a result, the method is environmentally friendly.

[0029] As used herein, the term "supersaturated solution" is understood to mean a solution that contains more solute than predicted by its solubility limit, i.e., the limit of the amount of solute that can be dissolved in a solvent at a particular temperature and / or pressure. For example, an aqueous solution that includes a phosphate source, such as a phosphate source described herein, and / or a fluoride source, such as a fluoride source described herein, can be supersaturated with respect to the phosphate source and / or the fluoride source. For example, an aqueous solution, such as a first aqueous solution described herein, can be supersaturated with respect to the phosphate source and / or the fluoride source at room temperature and / or atmospheric pressure. In a further example, a first aqueous solution described herein is provided that can be supersaturated with respect to the phosphate source and fluoride at room temperature and / or atmospheric pressure.

[0030] As used herein, the term "unsaturated solution" is understood to mean that the solute is present in the solution at a concentration lower than its solubility at equilibrium, e.g., equilibrium at room temperature and / or atmospheric pressure. For example, an aqueous solution comprising a calcium source as described herein, e.g., a second aqueous solution comprising a calcium source as described herein, can be unsaturated with respect to the calcium source.

[0031] The first and second aqueous solutions may be provided in equal size volumes. Further, the mixing in step c) is performed by adding the first and second aqueous solutions to a container, for example, simultaneously to the container.

[0032] The phosphate source may be selected from the group consisting of monosodium phosphate, disodium phosphate, trisodium phosphate, monosodium diphosphate, disodium diphosphate, trisodium diphosphate, tetrasodium diphosphate, and combinations thereof. For example, the phosphate source may include or consist of disodium phosphate, such as dibasic sodium phosphate dodecahydrate.

[0033] The fluoride source may comprise or consist of sodium fluoride and / or sodium bifluoride.

[0034] The calcium source may comprise or consist of calcium chloride and / or calcium phosphate.

[0035] The disclosure also provides a method as described herein, Step d) is present and / or Step e) is either present or absent.

[0036] The molar ratio of calcium source / phosphate source / fluoride source in the methods described herein can be about 2-10 / 3 / 1, such as 2.5 / 3 / 1 or 5 / 3 / 1.

[0037] The fluoroapatite crystals produced according to the methods described herein can be nano-fluoroapatite crystals, e.g., nano-fluoroapatite crystals having a maximum dimension, such as a length, in the range of about 1 nanometer to about 990 nanometers, e.g., about 25 nanometers to about 300 nanometers.

[0038] The first aqueous solution of the methods described herein may further include lactic acid. As a result, the fluoroapatite crystals formed may be microfluoroapatite crystals, e.g., microfluoroapatite crystals having a maximum dimension, e.g., a length, in the range of about 1 micrometer to about 20 micrometers, e.g., about 2 micrometers to about 20 micrometers.

[0039] The first aqueous solution of the method described herein may be obtained or is obtainable by applying heat and / or reduced pressure to an aqueous solution containing a phosphate source and a fluoride source, in this manner achieving supersaturation in a convenient manner.

[0040] Also provided are methods as described herein, wherein step h) is either present or absent.

[0041] The present disclosure also provides a method for preparing a dental or non-dental composition, the method comprising: (i) preparing fluoroapatite crystals according to the methods for producing fluoroapatite crystals described herein; (ii) mixing the fluorapatite crystals obtained in step (i) with an additive, thereby providing a dental or non-dental composition.

[0042] There is also provided the use of fluorapatite crystals produced according to the methods for preparing fluorapatite crystals described herein to make dental or non-dental compositions.

[0043] The additives described herein may include or consist of one or more of the following: polymers, adhesives such as dental adhesives, metal oxides such as zinc oxide and / or magnesium oxide.

[0044] The dental or non-dental compositions described herein may include or consist of one or more of the following: sealers, ceramic materials, dental restorative products, filling materials such as dental cement compositions, dental coatings, implants, medical devices. For example, the dental or non-dental compositions may include or consist of one or more of the following: liners such as microliners, ceramic materials.

[0045] The method for preparing fluorapatite crystals disclosed herein may be carried out as shown in FIG.

[0046] Further, the method for preparing the fluorapatite crystals described herein can be described as follows with reference to FIG.

[0047] In FIG. 1, the numbers have the following meaning: 100 represents the reactants. For example, the reactants may be provided as a first or second aqueous solution as described herein. 101 represents water or an aqueous solution of lactic acid as described herein. 102 represents a phosphate source and / or a fluoride source as described herein. For example, the phosphate source and / or the fluoride source may be provided as an aqueous solution containing a phosphate source. 103 represents water. 104 represents a calcium source as described herein, such as calcium chloride. For example, the calcium source may be provided as a second aqueous solution as described herein. 200 represents the reaction solution and / or stock solution. 201 represents the phosphate and fluoride source solution, or PFS. 202 represents a calcium source solution, i.e., CS. 300 represents a container. 400 represents filtration and / or washing and / or a filter. 500 represents the separation of by-products from the crystals and their storage. 501 represents a pump. 502 represents water and by-products. 503 represents a storage vessel for water and / or by-products. 600 represents drying and / or grinding. 601 represents the washing of the slurry. 602 represents dryness. 603 represents drying and collection of the powder. 604 represents a fine powder. 605 represents the storage of fine powder. 700 represents stored reactants and / or vessels and / or connections. The 800 represents a rolling band.

[0048] As with the method for producing fluorapatite described above, the reactants (100) used in the method described herein are based on those first proposed by Montel G in 1958. The phosphate source (102) may include sodium phosphate monohydrate, sodium phosphate monohydrate, sodium phosphate dihydrate, sodium phosphate dihydrate, sodium phosphate heptahydrate, sodium phosphate octahydrate, sodium phosphate dodecahydrate, sodium phosphate trihydrate anhydrous (cubic), sodium phosphate trihydrate anhydrous (hexagonal), sodium phosphate trihydrate hemihydrate, sodium phosphate trihydrate hexahydrate, sodium phosphate tridecahydrate, sodium diphosphate monohydrate, sodium diphosphate dihydrate anhydrous, sodium diphosphate dihydrate anhydrous, sodium diphosphate dihydrate hexahydrate, sodium diphosphate dihydrate anhydrous ... The calcium source (104) may include calcium chloride, calcium chloride dihydrate, calcium chloride hexahydrate, calcium phosphate, or combinations thereof. The fluoride source (102) may include sodium fluoride, sodium difluoride, or combinations thereof.

[0049] The reaction solutions (200) can be two, similar in volume, including a phosphate and fluoride source solution (PFS) (201) and a calcium source solution (CS) (202). The aforementioned solutions can be aqueous solutions. The PFS solution can be supersaturated and the CS can be undersaturated. A typical PFS solution can be composed of an aqueous solution of dibasic sodium phosphate (Na2HPO4), sodium fluoride (NaF), and lactic acid or water (101). When the components of the PFS are mixed in a separate vessel connected to the stored reactants (700), the resulting solution requires a heating period to reach supersaturation. Depending on the concentration of lactic acid, the required temperature varies from 35°C or 55°C. A typical CS solution is composed of calcium chloride (104), CaCl2, and water (103). The CS solution undergoes an exothermic period when calcium chloride is mixed with water. The temperature achieved instantaneously varies from 30°C to 55°C depending on the concentration of calcium chloride (CaCl2).

[0050] The reaction solutions may be stored as stock solutions (201 and 202), respectively, for industrially practical reasons. Mixing and stirring of the reaction solutions is carried out at room temperature, for example, about 20° C. to about 25° C., for example, 20° C.±2° C., in a separate vessel (700) connected to the stored stock solution (200). As used herein, room temperature contemplates a temperature of about 20° C. to about 25° C., for example, 20° C.±2° C.

[0051] In this vessel (300) the synthesis of nano- or micro-crystals takes place. The mixture may or may not be stirred (such as at about 100 rpm) depending on the desired size and morphology. In most cases, a white precipitate forms after stirring. Once the mixture is stirred, it can be heated to 70° C. and left at that temperature for about 10 minutes, or it can be filtered immediately after stirring depending on the desired size and morphology. This solution produced in the reaction vessel is then filtered and washed (400), the filter can be paper, polymeric, or metal-based. The filtration can use a pump (501) connected (700) to a water and by-products storage vessel (503), the water and by-products (502) are stored and then connected (700) to the filter (400). By that process the by-products are separated from the crystals and stored (500). After washing the slurry (601), a drying and grinding process (600) is carried out. This process (600) may be carried out on a rolling band (800) to facilitate the automation of the process. The drying process (602) may be carried out by reducing the pressure in a closed vessel containing the slurry, by centrifugation, by microwave radiation or by thermal radiation. The dried powder may then be collected (603) and transferred to a powder fin, i.e. a grinding device, which may only be required for nano-fluoroapatite powders for fine powders (604). Micro-fluoroapatite powders may not require grinding. Grinding may be carried out to separate agglomerated particles, if present. Furthermore, grinding allows the preparation of powders, e.g. fine powders. Once the fine powder is obtained, it may be stored (605) for further processing. EXAMPLES

[0052] The present disclosure is illustrated by the following non-limiting examples. Abbreviation SEM stands for Scanning Electron Microscopy. TEM stands for Transmission Electron Microscope. EDS stands for Energy Dispersive X-ray spectroscopy. XRD stands for X-ray diffraction or X-ray powder diffractogram. RS stands for Raman Spectroscopy. Ca stands for calcium. P stands for phosphorus. O stands for oxygen. Na stands for sodium. F stands for fluorine. PFS stands for phosphate and fluoride source solution. CS stands for calcium source solution. ISO stands for International organization for Standardization. mm stands for millimeter. nm stands for nanometer. μm stands for micrometer. LED stands for Light-Emitting Diode. MDP stands for methacryloyloxydecyl dihydrogen phosphate. MPa stands for Mega Pascal. rpm revolutions per minute w / w weight by weight

[0053] Example 1 The reactants used were calcium chloride (CaCl2, Sigma-Aldrich, lot number BCBS6619V), sodium phosphate dibasic dodecahydrate (Na2HPO4.12H2O, Sigma Life Science, lot number BCBX3841), and sodium fluoride (NaF, Sigma-Aldrich, lot number SLBK6350V). The calcium, phosphate, and fluoride reactants were used in a molar ratio of 2.5 / 3 / 1. The process was carried out as described above, with the PFS being supersaturated and the CS being undersaturated. The PFS and CS were mixed and stirred in the reaction vessel (300) for 1 minute at approximately room temperature (20° C.), and the mixture was immediately filtered (400), dried, and ground without additional heating (600).

[0054] The resulting powder was imaged using TEM (Figure 3A). The powder was also analyzed using XRD (Figure 4, graph 1) and RS (Figure 5, graph 1). In Figure 3A, crystalline rod-like individual crystals of about 40-60 nm length and 10-15 nm width can be observed. In Figure 4, graph 1, it can be observed that the diffractogram (Figure 4, graph 7) corresponding to the mineral fluorapatite (brown hexagonal prisms) from the Levant mine, St. Just, Cornwall, England, shows the same peaks and diffractogram pattern as Figure 4, graph 1 (Reference 13). The broadening of the peaks is a common phenomenon of nanoparticles. The obtained Raman spectrum (Figure 5, graph 1) is also equal to that observed in Figure 5, graph 7 corresponding to the mineral fluorapatite (light green hexagonal prisms) from Fulford, Eagle County, Colorado, USA (Reference 14).

[0055] Modifications were also carried out. The process was carried out as originally described, but with an additional heating at 70°C for 10 min immediately followed by stirring for 1 min at room temperature (20°C ± 2°C). The resulting powder was imaged using SEM (Figure 2A) and TEM (Figure 3B). The powder was also analyzed using XRD (Figure 4, graph 2), RS (Figure 5, graph 2), and EDS (Figure 6, graph 1). In Figures 2A and 3B, individual rod-shaped crystals of about 50-100 nm in length and 10-50 nm in width can be observed. In Figure 4, graph 2, it can also be seen that its diffractogram is equal to that of the mineral fluorapatite (Figure 4, graph 7). Its Raman spectrum (Figure 5, graph 2) is also equal to that observed for the mineral fluorapatite (Figure 5, graph 7). The EDS spectrum (Figure 6, graph 1) showed prominent peaks for O, Ca, P, F, and Na.

[0056] It was concluded that heating, for example at 70° C. for 10 minutes, slightly increased the size of the crystals.

[0057] Example 2 The reactants used were calcium chloride (CaCl2, Sigma-Aldrich, lot number BCBS6619V), dibasic sodium phosphate dodecahydrate (Na2HPO4.12H2O, Sigma Life Science, lot number BCBX3841), and sodium fluoride (NaF, Sigma-Aldrich, lot number SLBK6350V). The calcium, phosphate, and fluoride reactants were used in a molar ratio of 5 / 3 / 1. The process was carried out as previously described, with the PFS supersaturated and the CS undersaturated. The PFS and CS were mixed and stirred in a reaction vessel (designated 300 in Figure 1) at approximately room temperature (20°C) for 1 minute, and the mixture was immediately filtered (designated 400 in Figure 1), dried, and ground without additional heating (designated 600 in Figure 1).

[0058] The obtained powder was imaged using TEM (Figure 3C). The powder was also analyzed using XRD (Figure 4, graph 3) and RS (Figure 5, graph 3). In Figure 3C, crystalline rod-like individual crystals with a length of about 90-110 nm and a width of 30-60 nm can be observed. Graph 3 of Figure 4 shows an equivalent diffractogram as also displayed by the mineral fluorapatite (Figure 4, graph 7). It also shows that the broadening of the peaks is a general phenomenon of nanoparticles. The obtained Raman spectrum (Figure 5, graph 3) is also equivalent to the mineral fluorapatite.

[0059] Comparison with the powder obtained before heating in Example 1 shows that the crystals obtained in this example were larger than those obtained in Example 1. In the present case, the calcium, phosphate, and fluoride reactants were used in a molar ratio of 5 / 3 / 1, whereas in Example 1, the calcium, phosphate, and fluoride reactants were used in a molar ratio of 2.5 / 3 / 1. It therefore appears that the size of the obtained crystals can be influenced by the ratio of calcium source / phosphate source / fluoride source.

[0060] Additionally, the process was carried out as described above, but with 1 min of stirring at room temperature (20°C ± 2°C) followed immediately by additional heating at 70°C for 10 min. The resulting powder was imaged using SEM (Figure 2B) and TEM (Figure 3D). The powder was also analyzed using XRD (Figure 4, graph 4), RS (Figure 5, graph 4), and EDS (Figure 6, graph 2). In Figures 2B and 3D, individual rod-shaped crystals of about 100-150 nm in length and 40-90 nm in width can be observed. In Figure 4, graph 4, it can also be seen that its diffractogram is equivalent to that of the mineral fluorapatite (Figure 4, graph 7). Its Raman spectrum (Figure 5, graph 4) is also equivalent to that observed for the mineral fluorapatite (Figure 5, graph 7). The EDS spectrum (Figure 6, graph 2) showed prominent peaks for O, Ca, P, F, and Na.

[0061] It was concluded that heating, for example at 70° C. for 10 minutes, increases, for example slightly increases, the size of the crystals.

[0062] Example 3 The reactants used were calcium chloride (CaCl2, Sigma-Aldrich, lot number BCBS6619V), dibasic sodium phosphate dodecahydrate (Na2HPO4.12H2O, Sigma Life Science, lot number BCBX3841), and sodium fluoride (NaF, Sigma-Aldrich, lot number SLBK6350V). The calcium, phosphate, and fluoride reactants were used in a molar ratio of 5 / 3 / 1. The process was carried out as previously described, with the PFS supersaturated and the CS undersaturated. The PFS comprised an aqueous solution of lactic acid (DL-lactic acid, Sigma Life Science, 85% w / w, lot number MKBX6004V) at a concentration of 43% by weight of the PFS solution. The PFS and CS were mixed and stirred in a reaction vessel (designated 300 in Figure 1) at approximately room temperature (20°C) for 1 minute, and the mixture was heated to 70°C for 10 minutes. The mixture was then filtered (designated 400 in FIG. 1) and dried (designated 600 in FIG. 1).

[0063] The resulting powder was imaged using SEM (Figure 2C). The powder was also analyzed using XRD (Figure 4, graph 5), RS (Figure 5, graph 5), and EDS (Figure 6, graph 3). In Figure 2C, individual shuttle-like crystals of about 5.0 μm length and 1.0 μm width can be observed. In Figure 4, graph 5, it can also be seen that its diffractogram is equivalent to that of the mineral fluorapatite (Figure 4, graph 7). Its Raman spectrum (Figure 5, graph 5) is also equivalent to that observed for the mineral fluorapatite (Figure 5, graph 7). The EDS spectrum (Figure 6, graph 3) showed prominent peaks for O, Ca, P, F, and Na.

[0064] It was concluded that the presence of lactic acid allowed the formation of crystals with dimensions in the micrometer range.

[0065] Example 4 The reactants used were calcium chloride (CaCl2, Sigma-Aldrich, lot number BCBS6619V), dibasic sodium phosphate dodecahydrate (Na2HPO4.12H2O, Sigma Life Science, lot number BCBX3841), and sodium fluoride (NaF, Sigma-Aldrich, lot number SLBK6350V). The calcium, phosphate, and fluoride reactants were used in a molar ratio of 5 / 3 / 1. The process was carried out as previously described, with the PFS supersaturated and the CS undersaturated. The PFS comprised an aqueous solution of lactic acid (DL-lactic acid, Sigma Life Science, 85% w / w, lot number MKBX6004V) at a concentration of 19% by weight of the PFS solution. The PFS and CS were mixed without stirring at approximately room temperature (20° C.) in a reaction vessel (designated 300 in FIG. 1 ), and the mixture was heated to 70° C. for 10 minutes. The mixture was then filtered (designated 400 in FIG. 1) and dried (designated 600 in FIG. 1).

[0066] The resulting powder was imaged using SEM (Figure 2D). The powder was also analyzed using XRD (Figure 4, graph 6), RS (Figure 5, graph 6), and EDS (Figure 6, graph 4). In Figure 2D, individual dumbbell crystals of approximately 10.0 μm in length and 4.0 μm in width can be observed. In Figure 4, graph 6, it can also be seen that its diffractogram corresponds to that of the mineral fluorapatite (Figure 4, graph 7). Its Raman spectrum (Figure 5, graph 6) is also comparable to that observed for the mineral fluorapatite (Figure 5, graph 7). The EDS spectrum (Figure 6, graph 4) showed prominent peaks for O, Ca, P, F, and Na.

[0067] It was concluded that the presence of lactic acid allowed the formation of crystals with dimensions in the micrometer range.Furthermore, the amount of lactic acid appears to affect the size of the crystals formed.Furthermore, the lack of stirring appears to have affected the shape of the crystals, since in this case the crystals obtained were dumbbell-shaped, whereas the crystals in Example 3 had a shuttle-like shape.

[0068] Example 5 The powder obtained from Example 2, heated for an additional 10 minutes, was used to produce a polymer-based dental cement. The powder was silanized with 3-methacryloxypropyltrimethoxysilane (Carbosynth, lot number FM549142001) based on the method reported by Sousa et al. in 2003 (Reference 15). It was then mixed with Bis-GMA (Carbosynth, lot number FB1708012001) and TEGDMA (Carbosynth, lot number FT627491801) in a weight ratio of 70 / 30 on a surface preheated to 60°. The nano-fluorapatite powder represented 50% of the total weight of the cement. The activator was (+) Camphorquinone (Sigma-Aldrich, Lot No. 31H3611) and the accelerator 2-(Dimethylamino)ethyl methacrylate (Tokyo Chemical Industry, Lot No. ZKT2I-AT), both used at 0.1 wt% of the polymer portion of the cement. The cement was then polymerized using a dental curing LED lamp. The resulting polymerized material was white and slightly translucent. The RS spectrum of the polymerized cement is presented in Figure 7C. To control the bioactivity of the cement, 3.0 mm diameter, 1.0 mm thick pellets were immersed in deionized water and artificial saliva (so-called SAGF medium) at 37 °C for 1 week. The pellets were dried and then imaged using SEM. In Figure 7A, it can be observed that the nanorods are on the surface, but no additional features appear. The pellets soaked in artificial saliva exhibited needle-like and blade-like crystalline structures resulting from the interaction of the nano-fluorapatite rods with artificial saliva, demonstrating bioactivity (Figure 7B).

[0069] Biaxial flexural strength tests were performed according to ISO 4049:2019 (Dental - Polymer-based restorative materials). The average biaxial flexural strength was 61.1 (± 8.0) MPa, which exceeds the minimum flexural strength required for polymer-based dental cements. The hardness of the cements was also measured and compared to that of the flowable composite (Brilliant NanoFlow, Colthene Whaledent, lot number J68530). The hardness was 39.8 (± 4.4) HV1 for the nano-fluorapatite-polymer-based cement and 40.6 (± 2.7) HV1 for the flowable composite. The surface roughness of the nano-fluorapatite-polymer-based cement after polishing was also measured using interferometry and compared to that of the flowable composite. The average surface roughness (Sa) values ​​of the nano-fluorapatite-polymer-based cement were 0.19 (± 0.01) μm and 0.14 (± 0.02) μm for the flowable composite.

[0070] It was concluded that the crystals produced using the methods described herein may be used in the manufacture of dental cements, for example polymer-based dental cements.

[0071] Example 6 The powder from Example 2, heated for an additional 10 minutes, was used to modify the water-based cement. The nano-fluorapatite rods accounted for 20% of the weight of the reaction powder. The powder consisted of zinc oxide, magnesium oxide (Harvard cement, Harvard Dental, lot number 91605022), and nano-fluorapatite. Liquid with orthophosphoric acid (Harvard cement, Harvard Dental, lot number 1101609). The compressive strength of the cement was measured according to ISO 9917-1:2007 (Dental - Water-based cements - Part 1: Powder / liquid acid-based cements). The average compressive strength was 73.0 (± 5.5) MPa. This value exceeded the minimum flexural strength required for water-based dental cements. The RS spectrum of the modified water-based cement is presented in Figure 8C. To control the bioactivity of the cement, 3.0 mm diameter, 1.0 mm thick pellets were immersed in deionized water and artificial saliva (SAGF medium) at 37°C for 1 week. The pellets were dried and then imaged using SEM. In Figure 8A, it can be observed that the nanorods are on the surface, but no additional features appear. The pellets immersed in artificial saliva showed blade-like crystalline structures resulting from the interaction of the nano fluorapatite rods with the artificial saliva, indicating bioactivity (Figure 8B).

[0072] It was concluded that the crystals produced using the methods described herein may be used in the manufacture of dental cements, for example water-based dental cements.

[0073] Example 7 The powder from Example 2, heated for an additional 10 minutes, was mixed with different dental adhesives to create microliners: a self-etching ethanol-based 10-methacryloyloxydecyl dihydrogen phosphate (10-MDP)-containing adhesive (Allbond Universal, Bisco, lot number 180006141), a water-based 10-MDP-containing primer (Clearfil SE bond primer, Kuraray Noritake, lot number 1E0348, and an ethanol / water-free adhesive (Clearfil SE bond, Kuraray Noritake, lot number 3F0468), a total etch ethanol-based adhesive (Optibond Solo Plus, Kerr, lot number 7038740), and a total etch water-based adhesive (One Coat, Colthene Whaledent, lot number I89644).

[0074] To evaluate the bioactivity of the microliners, pellets of each mixture, 3.0 mm diameter and 1.0 mm thick, were immersed in deionized water and artificial saliva (SAGF medium) for one week at 37°C. The pellets were dried and then imaged using SEM. It can be observed that all mixtures immersed in deionized water (Figures 9A, 9C, 9E, 9G) did not show additional surface features compared to pellets immersed in artificial saliva (Figures 9B, 9D, 9F, 9H), resulting in the production of crystalline blade-like and needle-like structures. The EDS structures (Figures 10, graphs 1, 2, 3, 4) of the crystalline structures (Figures 9B, 9D, 9F, 9H) showed prominent peaks of O, Ca, P, F, and Na.

[0075] To exclude the negative effect of nano-fluorapatite crystals on the bond strength of each dental adhesive to human dentin, a shear bond strength test was performed. The test was based on ISO 29022:2013 (Dental-Adhesive-Notched Edge Shear Bond Strength Test). Nano-fluorapatite powder was mixed with different adhesives in a 1 / 1 weight ratio. The total Etch water-based adhesive showed a mean shear bond value of 17.1 (± 4.2) MPa (confidence interval: 14.9-19.5), and when mixed with nano-fluorapatite rods, the mean value was 17.5 (± 5.3) MPa (confidence interval: 14.6-20.4). The self-etch ethanol-based 10-MDP-containing adhesive showed a mean shear bond value of 20.1 (±4.6) MPa (confidence interval: 17.6-22.6) and when mixed with nano-fluoroapatite rods the mean value was 21.1 (±5.3) MPa (confidence interval: 18.4-24.3). The total-etch ethanol-based adhesive showed a mean shear bond value of 24.8 (±6.3) MPa (confidence interval: 21.2-28.2) and when mixed with nano-fluoroapatite rods the mean value was 26.2 (±4.5) MPa (confidence interval: 23.7-28.6). Finally, the system composed of water-based 10-MDP-containing primer and ethanol / water-free adhesive showed a mean shear bond value of 28.0 (± 5.3) MPa (confidence interval: 25.11-30.9), and when mixed with nano-fluorapatite rods, the mean value was 25.0 (± 3.6) MPa (confidence interval: 23.05-27.02). According to a two-tailed paired t-test, no statistically significant differences were found, thus ruling out a negative effect on the shear bond strength by including nano-fluorapatite crystals in the adhesive. TEM images of the adhesive interface are presented in Figure 11. Nano-fluorapatite rods were mixed with the self-etching ethanol-based 10-MDP-containing adhesive. A close package of crystals is observed in the adhesive. Also, the close contact with the dentin tissue results in the formation of a barrier or microliner.

[0076] It was concluded that the crystals produced using the methods described herein may be used in the manufacture of dental liners, such as dental microliners.

[0077] Example 8 The reactants used were calcium chloride (CaCl2, Sigma-Aldrich, lot number BCBS6619V), sodium phosphate dibasic dodecahydrate (Na2HPO4.12H2O, Sigma Life Science, lot number BCBX3841), and sodium fluoride (NaF, Sigma-Aldrich, lot number SLBK6350V). The calcium, phosphate, and fluoride reactants were used in a molar ratio of 5 / 3 / 1. The process was carried out as previously described, with the PFS supersaturated and the CS also supersaturated. The PFS and CS were mixed and stirred at 70 rpm for 1 minute at approximately room temperature (20° C.) in a reaction vessel (designated 300 in FIG. 1), and the mixture was immediately filtered (designated 400 in FIG. 1), dried, and ground without additional heating (designated 600 in FIG. 1). Only after stirring, no precipitate was formed immediately after mixing. Analysis using SEM showed the formation of some individual crystals, but overall the precipitate was not crystalline. The results of this example were compared with those obtained in Example 2, and it was concluded that CS must be undersaturated to obtain crystals.

[0078] References 1.Enax J, Janus AM, Raabe D, Epple M, Fabritius HO. Ultrastructural organization and micromechanical properties of shark tooth enameloid. Acta Biomaterialia.2014 Sep;10(9):3959-68. 2.Konttinen ML, HanhijaRjvi H.Fluoride concentrations of the surface enamel of children living in an optimally fluoridated community. European Journal of Oral Sciences.1986 Oct;94(5):427-35. 3.Muller F,Zeitz C,Mantz H,Ehses K-H,Soldera F,Schmauch J,et al.Elemental Depth Profiling of Fluoridated Hydroxyapatite: Saving Your Dentition by the Skin of Your Teeth? Langmuir.2010 Dec 21;26(24):18750-9. 4.Nedeljkovic I,De Munck J,Vanloy A,Declerck D,Lambrechts P,Peumans M,et al.Secondary caries: prevalence,characteristics,and approach.Clin Oral Investig.2020 Feb;24(2):683-91. 5.Montel G.Contribution al’etude des mecanismes de synthese de la fluorapatite.[Paris];1958. 6.Farr TD,Tarbutton G,Lewis HT. SYSTEM CaO-P 2 O 5 -HF-H 2 O: EQUILIBRIUM AT 25 AND 50° 1.The Journal of Physical Chemistry.1962 Feb;66(2):318-21. 7.Kniep R, Simon P.Fluorapatite-Gelatine-Nanocomposites: Self-Organized Morphogenesis,Real Structure and Relations to Natural Hard Materials.In: Naka K,editor.Biomineralization I[Internet].Springer Berlin Heidelberg;2006[cited 2016 May 17].p.73-125.(Topics in Current Chemistry). Available from: http: / / link.springer.com / chapter / 10.1007 / 128_053 8.Chen H,Tang Z,Liu J,Sun K,Chang S-R,Peters MC,et al. Acellular Synthesis of a Human Enamel-like Microstructure.Adv Mater.2006 Jul 18;18(14):1846-51. 9.Chen M,Jiang D,Li D,Zhu J,Li G,Xie J.Controllable synthesis of fluorapatite nanocrystals with various morphologies: Effects of pH value and chelating reagent.Journal of Alloys and Compounds.2009 Oct 19;485(1-2):396-401. 10. Clarkson BH, Chen H. Methods for production and use of synthetic hydroxyapatite and fluorapatite nanorods, and superstructures assembled from the same[Internet]. US7879388 B2, 2011[cited 2016 Sep 16]. Available from: http: / / www.google.se / patents / US7879388 11. Wang H, Sun K, Li A, Wang W, Chui P. Size-controlled synthesis and characterization of fluorapatite nanocrystals in the presence of gelatin. Powder Technology. 2011 May 15;209(1):9-14. 12. Furukawa A, 古川彰. Method for producing fluorapatite and method for producing fluorapatite particulate[Internet]. JP2014181160A, 2014[cited 2020 Nov 27]. Available from: https: / / patents.google.com / patent / JP2014181160A / en 13. Fluorapatite R060421-RRUFF Database: Raman, X-ray, Infrared, and Chemistry[Internet].[cited 2021 Jan 22]. Available from: https: / / rruff.info / fluorapatite / R060421 14.Apatite R050192-RRUFF Database:Raman,X-ray,Infrared,and Chemistry [Internet].[cited 2021 Jan 22].Available from:https: / / rruff.info / Apatite / R050192 15.Sousa RA,Reis RL,Cunha AM,Bevis MJ. Coupling of HDPE / hydroxyapatite composites by silane-based methodologies.J Mater Sci Mater Med.2003 Jun;14(6):475-87

Claims

1. Method for producing nano- or micro-fluorapatite crystals The method, a) providing a first aqueous solution, said first aqueous solution comprising: a phosphate source and a fluoride source; and optionally lactic acid; The first aqueous solution is supersaturated with respect to the phosphate source and the fluoride source. providing a first aqueous solution, b) providing a second aqueous solution comprising a calcium source, said second aqueous solution is unsaturated with respect to said calcium source; c) mixing the first aqueous solution with the second aqueous solution, thereby forming a nano-fluorinated apatite. providing a mixture containing fluorapatite crystals or micro fluorapatite crystals and a further aqueous solution; With d) optionally stirring the mixture of step c); e) optionally heating the mixture of step c) and / or step d); f) adding the nano- or micro-fluoroapatite crystals to the further water Separating it from the solution; g) Optionally, the nano-fluoroapatite crystals or micro-fluoroapatite crystals of step f) are drying the titute crystals; h) Optionally, the nano-fluoroapatite obtained in step f) or step g). and grinding the crystals or micro fluoroapatite crystals, When the first aqueous solution in step a) does not contain lactic acid, nano fluoroapatite crystals When the first aqueous solution in step a) contains lactic acid, Tight crystals are formed, the method.

2. 2. A method for producing nano fluoroapatite crystals according to claim 1, said method comprising: but, a) providing a first aqueous solution comprising a phosphate source and a fluoride source; The first aqueous solution is supersaturated with respect to the phosphate source and the fluoride source. providing a first aqueous solution, b) providing a second aqueous solution comprising a calcium source, said second aqueous solution is unsaturated with respect to said calcium source; c) mixing the first aqueous solution with the second aqueous solution, thereby forming a nano-fluorinated apatite. providing a mixture containing crystalline silicate and a further aqueous solution; d) optionally stirring the mixture of step c); e) optionally heating the mixture of step c) and / or step d); f) separating the nano fluoroapatite crystals from the further aqueous solution; g) optionally drying the nano fluoroapatite crystals of step f); h) Optionally, the nano-fluoroapatite obtained in step f) or step g). and crushing the crystals.

3. 2. A method for producing micro fluoroapatite crystals according to claim 1, comprising: The method is a) providing a first aqueous solution, said first aqueous solution comprising: a phosphate source and a fluoride source; Lactic acid, The first aqueous solution is supersaturated with respect to the phosphate source and the fluoride source. providing a first aqueous solution, b) providing a second aqueous solution comprising a calcium source, said second aqueous solution is unsaturated with respect to said calcium source; c) mixing the first aqueous solution with the second aqueous solution, thereby forming a microfluoride solution; providing a mixture comprising patite crystals and a further aqueous solution; d) optionally stirring the mixture of step c); e) optionally heating the mixture of step c) and / or step d); f) separating the micro-fluorapatite crystals from the further aqueous solution; g) optionally drying the micro fluoroapatite crystals of step f); 、 h) Optionally, the microapatite crystals obtained in step f) or step g) are and crushing the crystals.

4. the first aqueous solution and the second aqueous solution are provided in equal sized volumes; and / or teeth The mixing of step c) comprises adding the first aqueous solution and the second aqueous solution simultaneously to a container. The method according to any one of claims 1 to 3, wherein the method is carried out by

5. The phosphate source may be monosodium phosphate, disodium phosphate, trisodium phosphate Sodium, Monosodium Diphosphate, Disodium Diphosphate, Trisodium Diphosphate, Diphosphate 5. The method according to claim 1, wherein the carboxylic acid salt is selected from the group consisting of tetrasodium phosphate, ... The method according to any one of claims 1 to 5.

6. The phosphate source is disodium phosphate, e.g., dibasic sodium phosphate. The method of any one of claims 1 to 5, comprising a dihydrate.

7. The fluoride source is sodium fluoride and / or sodium difluoride. Item 7. The method according to any one of items 1 to 6.

8. The calcium source is Calcium chloride, and / or The method according to any one of claims 1 to 7, wherein the calcium phosphate is calcium phosphate.

9. step d) is present and / or The method according to any one of claims 1 to 8, wherein step e) is or is not present. Law.

10. The molar ratio of the calcium source to the phosphate source to the fluoride source is 2 Any of claims 1 to 9, wherein the ratio is from 1 to 10 / 3 / 1, for example 2.5 / 3 / 1 or 5 / 3 / 1.

13. The method according to claim 1.

11. The method according to any one of claims 1 to 10, wherein step h) is present.

12. The nano fluoroapatite crystals are 1 nanometer to 990 nanometers, for example 25 Claims 1, 2 or 4 having a maximum dimension in the range of nanometers to 300 nanometers 12. The method according to any one of claims 1 to 11.

13. The micro fluoroapatite crystals are 1 micrometer to 20 micrometers; For example, the claims have a maximum dimension in the range of 2 micrometers to 20 micrometers.

12. The method according to any one of claims 1 or 3 to 11.

14. The first aqueous solution is an aqueous solution containing the phosphate source and the fluoride source. Claims obtained or obtainable by application of heat and / or reduced pressure.

14. The method according to any one of 1 to 13.